2020
DOI: 10.1016/j.jjcc.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sleep apnea on right atrial structural remodeling with atrial fibrillation

Abstract: Background: Atrial remodeling associated with atrial fibrillation (AF) and sleep apnea is well known. Although sleep apnea is known to be associated with left atrial (LA) remodeling, its association with right atrial (RA) remodeling remains unclear. The study aimed to investigate the effect of sleep apnea on RA remodeling. Methods: We enrolled 141 AF patients who had undergone ablation. Sleep study results were evaluated using a portable sleep apnea test device. RA and LA volumes were determined by computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In addition, the impact of sleep apnea on recurrence may be considered in only the RA remodeling group without LA remodeling. We previously reported a correlation between RA structural remodeling and sleep apnea and showed that RA structural remodeling correlated with the severity of sleep apnea regardless of the AF type 16 . Importantly, previous studies have found that sleep apnea was a predictor of failure of rhythm control strategies, such as AF ablation 31 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, the impact of sleep apnea on recurrence may be considered in only the RA remodeling group without LA remodeling. We previously reported a correlation between RA structural remodeling and sleep apnea and showed that RA structural remodeling correlated with the severity of sleep apnea regardless of the AF type 16 . Importantly, previous studies have found that sleep apnea was a predictor of failure of rhythm control strategies, such as AF ablation 31 .…”
Section: Discussionmentioning
confidence: 93%
“…In the RA volume measurements, the inferior and superior vena cava at their ostia were manually excluded. In this study, we defined an atrial volume on CT of ≥110 mL as atrial structural remodeling based on receiver operating characteristic (ROC) analysis and previous reports 12‐16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, 118 participants (55.4%) had abnormal CAVI values (≥ 9). The patients with abnormal CAVI values were older and had higher CHADS2 scores, CHA2DS2VASc scores, mapping were performed in order to investigate the relationship between structural and electrical remodeling during SR, as previously described 18,19) . Voltage and activation timing was recorded in a bipolar contact map using the high-density circular mapping catheter.…”
Section: Comparison Of the Clinical Characteristics And Atrial Remodeling Parameters In Cavimentioning
confidence: 99%
“…A non-contact ablation protocol has been previously published. 16 Contact guide ablation using a TactiCath CF sensing catheter targeted to 10-40 g, catheter stability and CF waveforms were monitored visually, and the lesion size was target to the standard value (from 5 to 6 points). Esophageal temperature monitoring was performed in all patients.…”
mentioning
confidence: 99%